Interim buprenorphine treatment during delays to comprehensive treatment: Changes in psychiatric symptoms - Streck, Joanna M. (Exp Clin Psychopharmacol, 2018)
Prevalence of depression, anxiety and mood disorders among individuals with opioid use disorder far exceeds that of the general population. While psychiatric symptoms often improve upon entry into opioid treatment, this has typically been seen with treatments involving psychosocial counseling. In this secondary analysis, we examined changes in psychiatric symptoms during a randomized clinical trial evaluating an interim buprenorphine treatment without counseling among individuals awaiting entry into comprehensive treatment (Sigmon et al., 2016). Waitlisted adults with opioid use disorder (N=50) were randomized to one of two 12-week conditions: Interim Buprenorphine Treatment (IBT; N=25) consisting of buprenorphine maintenance using a computerized medication dispenser, with bi-monthly clinic visits and technology-assisted monitoring, or Waitlist Control (WLC; N=25) wherein participants remained on the waitlist of their local clinic. All participants completed assessments of psychiatric symptoms at intake and Study Weeks 4, 8 and 12. We examined changes on the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI-II), Brief Symptom Inventory (BSI), and Psychiatric subscale of the Addiction Severity Index (ASI). Significant group by time interactions were observed for all measures of psychiatric severity examined: BAI (p<.05), BDI-II (p<.01), six BSI subscales (p’s<.05), and the ASI Psychiatric subscale (p<.05). On all measures, IBT participants reported significantly reduced psychiatric severity at the 4-, 8- and 12-week assessments relative to baseline. In contrast, there were no significant changes in psychiatric symptoms among WLC participants. IBT without counseling may improve psychiatric distress among waitlisted individuals with opioid use disorder.